Hubungan antara Penyesuaian diri dan Kontrol diri dengan Perilaku Delikuen pada siswa SMA Muhammadiyah 1 Jombang - Haryanti Tri Darmi Titisari (Universitas Katolik Soegijapranata, 2017)
Adolescence is a transitional period in physical and psychological development that is influenced by several factors including the environment. Self-control and self-adjustment have an important role in the development so that adolescents do not have a tendency to behave delinquently when they are in the new community and environment. On this basis, this study aims to determine the relationship between self-control and self-adjustment with delinquency behavior in adolescents. The population in this study was students of grade 10th, and sampling was taken by using saturation sampling technique for 98 students and using self-control questionnaire, adjustment, and delinquency behavior. Statistics applied Spearman correlation technique and data were processed by using computer program SPSS series 22 for IBM for Windows. The result of the analysis shows the significance value was 0.721, and the correlation coefficient was -0.037 between Self-control with Delinquency, as well as the significance value of 0.345 and the correlation coefficient of -0.096 in Self-Adjustment with Delinquency (p> 0.05). This indicates that there was no significant relationship between Self-Control and Adjustment to Delinquency behavior.